Psychometric properties of the Bangla version of the sense of coherence scale among university students in Bangladesh. - Momtaz Sultana; Yuta Hayashi; Tanzilur Rahman Tamim; Rie Chiba; Muhammad Kamal Uddin (PLoS ONE)
Introduction Sense of coherence is a key concept in psychological science that contributes to mental health by helping people cope with various stressors in their daily lives. A literature review demonstrated the unavailability of a tool for measuring sense of coherence in Bangladesh. This study aimed to translate the 13-item Sense of Coherence scale (SOC-13) into the Bangla language and to examine its validity, dimensionality, and reliability. Method After translating the SOC-13, a cross-sectional online survey was conducted with 510 undergraduate students at a university in Bangladesh from July to October 2021. Construct validity was assessed through confirmatory factor analysis to analyze the structural validity of the Bangla SOC-13 scale, and by examining correlations with related constructs (self-esteem, well-being, and psychological distress). The alpha coefficient was calculated to examine internal consistency. Data were analyzed using SPSS version 22 and R statistical software. Results A total of 320 respondents provided valid responses (response rate: 62.7%). The structural validity of the SOC-13, as examined through confirmatory factor analysis, was consistent across studies (a three-factor structure with an acceptable fit), and convergent validity was evidenced through a statistically significant positive relationships between sense of coherence and both self-esteem and well-being, as well as criterion validity was supported by a significant negative relationship with psychological distress. The internal consistency of the total scores by the coefficient alpha was good (α =  0.74), whereas the alphas of each subscale showed mediocre to fair reliability. Conclusion The Bangla version of the SOC-13 showed good construct validity, acceptable criterion validity, and good reliability based on overall internal consistency. Thus, it can be used to assess sense of coherence in young adults, although there is scope for further examination.